Éssai de synthèse paléogéographique et paléobiostratigraphique du bassin occidental portugais au cours du crétacé supérieur - Berthou, P. (2008)
The Upper-Cretaceous transgressive serie is described by the authors, on the whole Occidental Portuguese Basin: it begins in the Lisbon region in the Albian and finishes in the Beira litoral province in the lower Turonian, while the sedimentation zones migrate Northward. The lithologic composition is given for each stage and sub-stage, taking into cgnsideration, in particular in the Upper Cenomanian, the lateral variations from one region to another. The paleogeography becomes clear by the study of the sedimentation environments (6 fig.). In conclusion, the authors propose a correlation between the whole serie and the accepted zonation of the Northwestern Europe. Tables show the repartition of the main macrofauna and microfauna.